Bioinspired Chemical Communication between Synthetic Nanomotors. Issue 1 (4th December 2017) - Chen, Chuanrui; Chang, Xiaocong; Teymourian, Hazhir; Ramírez‐Herrera, Doris E.; Esteban‐Fernández de Ávila, Berta; Lu, Xiaolong; Li, Jinxing; He, Sha; Fang, Chengcheng; Liang, Yuyan; Mou, Fangzhi; Guan, Jianguo; et al.
Abstract: While chemical communication plays a key role in diverse natural processes, the intelligent chemical communication between synthetic nanomotors remains unexplored. The design and operation of bioinspired synthetic nanomotors is presented. Chemical communication between nanomotors is possible and has an influence on propulsion behavior. A chemical "message" is sent from a moving activator motor to a nearby activated (receiver) motor by release of Ag + ions from a Janus polystyrene/Ni/Au/Ag activator motor to the activated Janus SiO2 /Pt nanomotor. The transmitted silver signal is translated rapidly into a dramatic speed change associated with the enhanced catalytic activity of activated motors. Selective and successive activation of multiple nanomotors is achieved by sequential localized chemical communications. The concept of establishing chemical communication between different synthetic nanomotors paves the way to intelligent nanoscale robotic systems that are capable of cooperating with each other. Abstract : The Ghost in the Machine : Release of Ag + ions from a Janus polystyrene/Ni/Au/Ag activator motor immersed in hydrogen peroxide (H2 O2 ) solution affects the motion behavior of neighboring Janus SiO2 /Pt nanomotors. As a consequence of an instantaneous enhancement in catalytic H2 O2 decomposition, receiver motors (SiO2 /Pt nanomotors) respond to local Ag + ions by dramatically altering their propulsion speed.